(* Title: HOL/ex/veriT_Preprocessing.thy
Author: Jasmin Christian Blanchette, Inria, LORIA, MPII
*)
section \<open>Proof Reconstruction for veriT's Preprocessing\<close>
theory veriT_Preprocessing
imports Main
begin
declare [[eta_contract = false]]
lemma
some_All_iffI: "p (SOME x. \<not> p x) = q \<Longrightarrow> (\<forall>x. p x) = q" and
some_Ex_iffI: "p (SOME x. p x) = q \<Longrightarrow> (\<exists>x. p x) = q"
by (metis (full_types) someI_ex)+
ML \<open>
fun mk_prod1 bound_Ts (t, u) =
HOLogic.pair_const (fastype_of1 (bound_Ts, t)) (fastype_of1 (bound_Ts, u)) $ t $ u;
fun mk_tuple1 bound_Ts = the_default HOLogic.unit o try (foldr1 (mk_prod1 bound_Ts));
fun mk_arg_congN 0 = refl
| mk_arg_congN 1 = arg_cong
| mk_arg_congN 2 = @{thm arg_cong2}
| mk_arg_congN n = arg_cong RS funpow (n - 2) (fn th => @{thm cong} RS th) @{thm cong};
fun mk_let_iffNI ctxt n =
let
val ((As, [B]), _) = ctxt
|> Ctr_Sugar_Util.mk_TFrees n
||>> Ctr_Sugar_Util.mk_TFrees 1;
val ((((ts, us), [p]), [q]), _) = ctxt
|> Ctr_Sugar_Util.mk_Frees "t" As
||>> Ctr_Sugar_Util.mk_Frees "u" As
||>> Ctr_Sugar_Util.mk_Frees "p" [As ---> B]
||>> Ctr_Sugar_Util.mk_Frees "q" [B];
val tuple_t = HOLogic.mk_tuple ts;
val tuple_T = fastype_of tuple_t;
val lambda_t = HOLogic.tupled_lambda tuple_t (list_comb (p, ts));
val lambda_T = fastype_of lambda_t;
val left_prems = map2 (curry Ctr_Sugar_Util.mk_Trueprop_eq) ts us;
val right_prem = Ctr_Sugar_Util.mk_Trueprop_eq (list_comb (p, us), q);
val concl = Ctr_Sugar_Util.mk_Trueprop_eq
(Const (@{const_name Let}, tuple_T --> lambda_T --> B) $ tuple_t $ lambda_t, q);
val goal = Logic.list_implies (left_prems @ [right_prem], concl);
val vars = Variable.add_free_names ctxt goal [];
in
Goal.prove_sorry ctxt vars [] goal (fn {context = ctxt, ...} =>
HEADGOAL (hyp_subst_tac ctxt) THEN
Local_Defs.unfold0_tac ctxt @{thms Let_def prod.case} THEN
HEADGOAL (resolve_tac ctxt [refl]))
end;
datatype rule_name =
Refl
| Taut of thm
| Trans of term
| Cong
| Bind
| Sko_Ex
| Sko_All
| Let of term list;
fun str_of_rule_name Refl = "Refl"
| str_of_rule_name (Taut th) = "Taut[" ^ @{make_string} th ^ "]"
| str_of_rule_name (Trans t) = "Trans[" ^ Syntax.string_of_term @{context} t ^ "]"
| str_of_rule_name Cong = "Cong"
| str_of_rule_name Bind = "Bind"
| str_of_rule_name Sko_Ex = "Sko_Ex"
| str_of_rule_name Sko_All = "Sko_All"
| str_of_rule_name (Let ts) =
"Let[" ^ commas (map (Syntax.string_of_term @{context}) ts) ^ "]";
datatype node = N of rule_name * node list;
fun lambda_count (Abs (_, _, t)) = lambda_count t + 1
| lambda_count ((t as Abs _) $ _) = lambda_count t - 1
| lambda_count ((t as Const (@{const_name case_prod}, _) $ _) $ _) = lambda_count t - 1
| lambda_count (Const (@{const_name case_prod}, _) $ t) = lambda_count t - 1
| lambda_count _ = 0;
fun zoom apply =
let
fun zo 0 bound_Ts (Abs (r, T, t), Abs (s, U, u)) =
let val (t', u') = zo 0 (T :: bound_Ts) (t, u) in
(lambda (Free (r, T)) t', lambda (Free (s, U)) u')
end
| zo 0 bound_Ts ((t as Abs (_, T, _)) $ arg, u) =
let val (t', u') = zo 1 (T :: bound_Ts) (t, u) in
(t' $ arg, u')
end
| zo 0 bound_Ts ((t as Const (@{const_name case_prod}, _) $ _) $ arg, u) =
let val (t', u') = zo 1 bound_Ts (t, u) in
(t' $ arg, u')
end
| zo 0 bound_Ts tu = apply bound_Ts tu
| zo n bound_Ts (Const (@{const_name case_prod},
Type (@{type_name fun}, [Type (@{type_name fun}, [A, Type (@{type_name fun}, [B, _])]),
Type (@{type_name fun}, [AB, _])])) $ t, u) =
let
val (t', u') = zo (n + 1) bound_Ts (t, u);
val C = range_type (range_type (fastype_of t'));
in
(Const (@{const_name case_prod}, (A --> B --> C) --> AB --> C) $ t', u')
end
| zo n bound_Ts (Abs (s, T, t), u) =
let val (t', u') = zo (n - 1) (T :: bound_Ts) (t, u) in
(Abs (s, T, t'), u')
end
| zo _ _ (t, u) = raise TERM ("zoom", [t, u]);
in
zo 0 []
end;
fun apply_Trans_left t (lhs, _) = (lhs, t);
fun apply_Trans_right t (_, rhs) = (t, rhs);
fun apply_Cong ary j (lhs, rhs) =
(case apply2 strip_comb (lhs, rhs) of
((c, ts), (d, us)) =>
if c aconv d andalso length ts = ary andalso length us = ary then (nth ts j, nth us j)
else raise TERM ("apply_Cong", [lhs, rhs]));
fun apply_Bind (lhs, rhs) =
(case (lhs, rhs) of
(Const (@{const_name All}, _) $ Abs (_, T, t), Const (@{const_name All}, _) $ Abs (s, U, u)) =>
(Abs (s, T, t), Abs (s, U, u))
| (Const (@{const_name Ex}, _) $ t, Const (@{const_name Ex}, _) $ u) => (t, u)
| _ => raise TERM ("apply_Bind", [lhs, rhs]));
fun apply_Sko_Ex (lhs, rhs) =
(case lhs of
Const (@{const_name Ex}, _) $ (t as Abs (_, T, _)) =>
(t $ (HOLogic.choice_const T $ t), rhs)
| _ => raise TERM ("apply_Sko_Ex", [lhs]));
fun apply_Sko_All (lhs, rhs) =
(case lhs of
Const (@{const_name All}, _) $ (t as Abs (s, T, body)) =>
(t $ (HOLogic.choice_const T $ Abs (s, T, HOLogic.mk_not body)), rhs)
| _ => raise TERM ("apply_Sko_All", [lhs]));
fun apply_Let_left ts j (lhs, _) =
(case lhs of
Const (@{const_name Let}, _) $ t $ _ =>
let val ts0 = HOLogic.strip_tuple t in
(nth ts0 j, nth ts j)
end
| _ => raise TERM ("apply_Let_left", [lhs]));
fun apply_Let_right ts bound_Ts (lhs, rhs) =
let val t' = mk_tuple1 bound_Ts ts in
(case lhs of
Const (@{const_name Let}, _) $ _ $ u => (u $ t', rhs)
| _ => raise TERM ("apply_Let_right", [lhs, rhs]))
end;
fun reconstruct_proof ctxt (lrhs as (_, rhs), N (rule_name, prems)) =
let
val goal = HOLogic.mk_Trueprop (HOLogic.mk_eq lrhs);
val ary = length prems;
val _ = warning (Syntax.string_of_term @{context} goal);
val _ = warning (str_of_rule_name rule_name);
val parents =
(case (rule_name, prems) of
(Refl, []) => []
| (Taut _, []) => []
| (Trans t, [left_prem, right_prem]) =>
[reconstruct_proof ctxt (zoom (K (apply_Trans_left t)) lrhs, left_prem),
reconstruct_proof ctxt (zoom (K (apply_Trans_right t)) (rhs, rhs), right_prem)]
| (Cong, _) =>
map_index (fn (j, prem) => reconstruct_proof ctxt (zoom (K (apply_Cong ary j)) lrhs, prem))
prems
| (Bind, [prem]) => [reconstruct_proof ctxt (zoom (K apply_Bind) lrhs, prem)]
| (Sko_Ex, [prem]) => [reconstruct_proof ctxt (zoom (K apply_Sko_Ex) lrhs, prem)]
| (Sko_All, [prem]) => [reconstruct_proof ctxt (zoom (K apply_Sko_All) lrhs, prem)]
| (Let ts, prems) =>
let val (left_prems, right_prem) = split_last prems in
map2 (fn j => fn prem =>
reconstruct_proof ctxt (zoom (K (apply_Let_left ts j)) lrhs, prem))
(0 upto length left_prems - 1) left_prems @
[reconstruct_proof ctxt (zoom (apply_Let_right ts) lrhs, right_prem)]
end
| _ => raise Fail ("Invalid rule: " ^ str_of_rule_name rule_name ^ "/" ^
string_of_int (length prems)));
val rule_thms =
(case rule_name of
Refl => [refl]
| Taut th => [th]
| Trans _ => [trans]
| Cong => [mk_arg_congN ary]
| Bind => @{thms arg_cong[of _ _ All] arg_cong[of _ _ Ex]}
| Sko_Ex => [@{thm some_Ex_iffI}]
| Sko_All => [@{thm some_All_iffI}]
| Let ts => [mk_let_iffNI ctxt (length ts)]);
val num_lams = lambda_count rhs;
val conged_parents = map (funpow num_lams (fn th => th RS fun_cong)
#> Local_Defs.unfold0 ctxt @{thms prod.case}) parents;
in
Goal.prove_sorry ctxt [] [] goal (fn {context = ctxt, ...} =>
Local_Defs.unfold0_tac ctxt @{thms prod.case} THEN
HEADGOAL (REPEAT_DETERM_N num_lams o resolve_tac ctxt [ext] THEN'
resolve_tac ctxt rule_thms THEN'
K (Local_Defs.unfold0_tac ctxt @{thms prod.case}) THEN'
EVERY' (map (resolve_tac ctxt o single) conged_parents)))
end;
\<close>
ML \<open>
val proof0 =
((@{term "\<exists>x :: nat. p x"},
@{term "p (SOME x :: nat. p x)"}),
N (Sko_Ex, [N (Refl, [])]));
reconstruct_proof @{context} proof0;
\<close>
ML \<open>
val proof1 =
((@{term "\<not> (\<forall>x :: nat. \<exists>y :: nat. p x y)"},
@{term "\<not> (\<exists>y :: nat. p (SOME x :: nat. \<not> (\<exists>y :: nat. p x y)) y)"}),
N (Cong, [N (Sko_All, [N (Bind, [N (Refl, [])])])]));
reconstruct_proof @{context} proof1;
\<close>
ML \<open>
val proof2 =
((@{term "\<forall>x :: nat. \<exists>y :: nat. \<exists>z :: nat. p x y z"},
@{term "\<forall>x :: nat. p x (SOME y :: nat. \<exists>z :: nat. p x y z)
(SOME z :: nat. p x (SOME y :: nat. \<exists>z :: nat. p x y z) z)"}),
N (Bind, [N (Sko_Ex, [N (Sko_Ex, [N (Refl, [])])])]));
reconstruct_proof @{context} proof2
\<close>
ML \<open>
val proof3 =
((@{term "\<forall>x :: nat. \<exists>x :: nat. \<exists>x :: nat. p x x x"},
@{term "\<forall>x :: nat. p (SOME x :: nat. p x x x) (SOME x. p x x x) (SOME x. p x x x)"}),
N (Bind, [N (Sko_Ex, [N (Sko_Ex, [N (Refl, [])])])]));
reconstruct_proof @{context} proof3
\<close>
ML \<open>
val proof4 =
((@{term "\<forall>x :: nat. \<exists>x :: nat. \<exists>x :: nat. p x x x"},
@{term "\<forall>x :: nat. \<exists>x :: nat. p (SOME x :: nat. p x x x) (SOME x. p x x x) (SOME x. p x x x)"}),
N (Bind, [N (Bind, [N (Sko_Ex, [N (Refl, [])])])]));
reconstruct_proof @{context} proof4
\<close>
ML \<open>
val proof5 =
((@{term "\<forall>x :: nat. q \<and> (\<exists>x :: nat. \<exists>x :: nat. p x x x)"},
@{term "\<forall>x :: nat. q \<and>
(\<exists>x :: nat. p (SOME x :: nat. p x x x) (SOME x. p x x x) (SOME x. p x x x))"}),
N (Bind, [N (Cong, [N (Refl, []), N (Bind, [N (Sko_Ex, [N (Refl, [])])])])]));
reconstruct_proof @{context} proof5
\<close>
ML \<open>
val proof6 =
((@{term "\<not> (\<forall>x :: nat. p \<and> (\<exists>x :: nat. \<forall>x :: nat. q x x))"},
@{term "\<not> (\<forall>x :: nat. p \<and>
(\<exists>x :: nat. q (SOME x :: nat. \<not> q x x) (SOME x. \<not> q x x)))"}),
N (Cong, [N (Bind, [N (Cong, [N (Refl, []), N (Bind, [N (Sko_All, [N (Refl, [])])])])])]));
reconstruct_proof @{context} proof6
\<close>
ML \<open>
val proof7 =
((@{term "\<not> \<not> (\<exists>x. p x)"},
@{term "\<not> \<not> p (SOME x. p x)"}),
N (Cong, [N (Cong, [N (Sko_Ex, [N (Refl, [])])])]));
reconstruct_proof @{context} proof7
\<close>
ML \<open>
val proof8 =
((@{term "\<not> \<not> (let x = Suc x in x = 0)"},
@{term "\<not> \<not> Suc x = 0"}),
N (Cong, [N (Cong, [N (Let [@{term "Suc x"}], [N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof8
\<close>
ML \<open>
val proof9 =
((@{term "\<not> (let x = Suc x in x = 0)"},
@{term "\<not> Suc x = 0"}),
N (Cong, [N (Let [@{term "Suc x"}], [N (Refl, []), N (Refl, [])])]));
reconstruct_proof @{context} proof9
\<close>
ML \<open>
val proof10 =
((@{term "\<exists>x :: nat. p (x + 0)"},
@{term "\<exists>x :: nat. p x"}),
N (Bind, [N (Cong, [N (Taut @{thm add_0_right}, [])])]));
reconstruct_proof @{context} proof10;
\<close>
ML \<open>
val proof11 =
((@{term "\<not> (let (x, y) = (Suc y, Suc x) in y = 0)"},
@{term "\<not> Suc x = 0"}),
N (Cong, [N (Let [@{term "Suc y"}, @{term "Suc x"}], [N (Refl, []), N (Refl, []),
N (Refl, [])])]));
reconstruct_proof @{context} proof11
\<close>
ML \<open>
val proof12 =
((@{term "\<not> (let (x, y) = (Suc y, Suc x); (u, v, w) = (y, x, y) in w = 0)"},
@{term "\<not> Suc x = 0"}),
N (Cong, [N (Let [@{term "Suc y"}, @{term "Suc x"}], [N (Refl, []), N (Refl, []),
N (Let [@{term "Suc x"}, @{term "Suc y"}, @{term "Suc x"}],
[N (Refl, []), N (Refl, []), N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof12
\<close>
ML \<open>
val proof13 =
((@{term "\<not> \<not> (let x = Suc x in x = 0)"},
@{term "\<not> \<not> Suc x = 0"}),
N (Cong, [N (Cong, [N (Let [@{term "Suc x"}], [N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof13
\<close>
ML \<open>
val proof14 =
((@{term "let (x, y) = (f (a :: nat), b :: nat) in x > a"},
@{term "f (a :: nat) > a"}),
N (Let [@{term "f (a :: nat) :: nat"}, @{term "b :: nat"}],
[N (Cong, [N (Refl, [])]), N (Refl, []), N (Refl, [])]));
reconstruct_proof @{context} proof14
\<close>
ML \<open>
val proof15 =
((@{term "let x = (let y = g (z :: nat) in f (y :: nat)) in x = Suc 0"},
@{term "f (g (z :: nat) :: nat) = Suc 0"}),
N (Let [@{term "f (g (z :: nat) :: nat) :: nat"}],
[N (Let [@{term "g (z :: nat) :: nat"}], [N (Refl, []), N (Refl, [])]), N (Refl, [])]));
reconstruct_proof @{context} proof15
\<close>
ML \<open>
val proof16 =
((@{term "a > Suc b"},
@{term "a > Suc b"}),
N (Trans @{term "a > Suc b"}, [N (Refl, []), N (Refl, [])]));
reconstruct_proof @{context} proof16
\<close>
thm Suc_1
thm numeral_2_eq_2
thm One_nat_def
ML \<open>
val proof17 =
((@{term "2 :: nat"},
@{term "Suc (Suc 0) :: nat"}),
N (Trans @{term "Suc 1"}, [N (Taut @{thm Suc_1[symmetric]}, []), N (Cong,
[N (Taut @{thm One_nat_def}, [])])]));
reconstruct_proof @{context} proof17
\<close>
ML \<open>
val proof18 =
((@{term "let x = a in let y = b in Suc x + y"},
@{term "Suc a + b"}),
N (Trans @{term "let y = b in Suc a + y"},
[N (Let [@{term "a :: nat"}], [N (Refl, []), N (Refl, [])]),
N (Let [@{term "b :: nat"}], [N (Refl, []), N (Refl, [])])]));
reconstruct_proof @{context} proof18
\<close>
ML \<open>
val proof19 =
((@{term "\<forall>x. let x = f (x :: nat) :: nat in g x"},
@{term "\<forall>x. g (f (x :: nat) :: nat)"}),
N (Bind, [N (Let [@{term "f :: nat \<Rightarrow> nat"} $ Bound 0],
[N (Refl, []), N (Refl, [])])]));
reconstruct_proof @{context} proof19
\<close>
ML \<open>
val proof20 =
((@{term "\<forall>x. let y = Suc 0 in let x = f (x :: nat) :: nat in g x"},
@{term "\<forall>x. g (f (x :: nat) :: nat)"}),
N (Bind, [N (Let [@{term "Suc 0"}], [N (Refl, []), N (Let [@{term "f (x :: nat) :: nat"}],
[N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof20
\<close>
ML \<open>
val proof21 =
((@{term "\<forall>x :: nat. let x = f x :: nat in let y = x in p y"},
@{term "\<forall>z :: nat. p (f z :: nat)"}),
N (Bind, [N (Let [@{term "f (z :: nat) :: nat"}],
[N (Refl, []), N (Let [@{term "f (z :: nat) :: nat"}],
[N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof21
\<close>
ML \<open>
val proof22 =
((@{term "\<forall>x :: nat. let x = f x :: nat in let y = x in p y"},
@{term "\<forall>x :: nat. p (f x :: nat)"}),
N (Bind, [N (Let [@{term "f (x :: nat) :: nat"}],
[N (Refl, []), N (Let [@{term "f (x :: nat) :: nat"}],
[N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof22
\<close>
ML \<open>
val proof23 =
((@{term "\<forall>x :: nat. let (x, a) = (f x :: nat, 0 ::nat) in let y = x in p y"},
@{term "\<forall>z :: nat. p (f z :: nat)"}),
N (Bind, [N (Let [@{term "f (z :: nat) :: nat"}, @{term "0 :: nat"}],
[N (Refl, []), N (Refl, []), N (Let [@{term "f (z :: nat) :: nat"}],
[N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof23
\<close>
ML \<open>
val proof24 =
((@{term "\<forall>x :: nat. let (x, a) = (f x :: nat, 0 ::nat) in let y = x in p y"},
@{term "\<forall>x :: nat. p (f x :: nat)"}),
N (Bind, [N (Let [@{term "f (x :: nat) :: nat"}, @{term "0 :: nat"}],
[N (Refl, []), N (Refl, []), N (Let [@{term "f (x :: nat) :: nat"}],
[N (Refl, []), N (Refl, [])])])]));
reconstruct_proof @{context} proof24
\<close>
end